Strand 2: SCHEMA: Network Computers, ISDN, Learning and Social Networks, Network Computers and Learning - Timms, DWGT; Booth, SP (Proceedings of the International Conference on Networked Learning, 1998)
SCHEMA aims to investigate the use of multimedia telematics co deliver and support a series of training modules oriented cowards the continuing professional development needs of nursing, education and social work professionals living and working in high priority regions of Scotland, Germany, Sweden and Finland. Particular attention will be paid to the functionality of Net Computers (NCs™) connected by Euro-ISDN, as vehicles for an educational environment which stresses collaboration and interaction. In addition to evaluating the technical viability of client-server topologies for delivering and supporting educational multimedia, SCHEMA will examine the nature of the learning processes involved and the implications of electronic communities for social integration.